UCI sports nutrition project: Nutritional periodization: Strategies to enhance training adaptation and recovery - Morton, J. P.; Hearris, M.; Fell, M. J.; Owens, D. J.; Halson, S.; Trommelen, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
The fundamental goal of nutrition for training is to provide the required energy and substrate to sustain the target training volume and intensity that is necessary to induce desired physiological adaptations. However, aside from fueling and recovery, it is now recognized that nutrient availability also modulates the activation of cell signaling pathways that regulate adaptations associated with both endurance and strength training. Such developments are the guiding principles underpinning "nutritional periodization" wherein energy, macronutrient, and micronutrient availability are deliberately manipulated across the microcycle, mesocycle, and macrocycle with the strategic goal to promote training adaptations, support recovery, manipulate body composition, and optimize competition performance. In addition to total "daily" nutrient intake, the elite athlete must, therefore, adjust their energy and carbohydrate intake in a meal-by-meal and day-by-day manner (i.e., carbohydrate periodization) in accordance with the energetic demands and training objectives of each specific training session. In addition to fueling (and refueling) for the work required, daily protein intake should at least be 1.6-2.1 g·kg -1 ·day -1 not only to account for amino acid oxidation during exercise but also, importantly, to promote tissue remodeling, notably skeletal muscle. Emerging evidence also supports the rationale for nutraceuticals to promote recovery and sleep, though the potential effect of such compounds in blunting training adaptation should also be considered. Taken together, it is increasingly clear that nutrition is a critical enabler to successful training outcomes, and as such, the sport nutritionist should be considered an integral member of an athlete`s coaching and performance support team.